Bone formation around two titanium implant surfaces placed in bone defects with and without a bone substitute material: A histological, histomorphometric, and micro-computed tomography evaluation - Trento, Guilherme [UNESP]; A. Carvalho, Pedro Henrique de [UNESP]; C. Reis, Erik N. R. de; Spin-Neto, Rubens [UNESP]; Bassi, Ana Paula F.; Pereira-Filho, Valfrido Antonio [UNESP] (Wiley-Blackwell, 2020)
Objective To evaluate the histological and microtomographic response of peri-implant bone tissue around titanium implants with different surface treatments, placed in bone defects filled or not filled with bone substitute materials. Materials and Methods Thirty rabbits were divided into two groups according to the implant surface treatment. A bone defect was created in both tibias of all the rabbits, followed by the placement of one implant in each of these defects. On the left tibia, the defect was filled with a blood clot (BC), and on the right tibia, the defect was filled with biphasic hydroxyapatite/beta-tricalcium-phosphate (HA/TCP); thus, there were four groups in total: BC-N: bone defect filled with a BC and porous surface titanium implant (control group); BC-A: bone defect filled with a BC and porous-hydrophilic surface titanium implant; HA/TCP-N: bone defect filled with a bone substitute material and porous surface titanium implant; HA/TCP-A: bone defect filled with a bone substitute material and porous-hydrophilic surface titanium implant. The animals were submitted for euthanasia at three distinct periods: 15, 30, and 60 days after implant installation. The samples were evaluated histologically and histometrically, to assess the quantity and quality of cells and the remaining bone substitute material in the grafted areas. The bone quantity was assessed by micro-computed tomography (CT). Results For both surface types, the presence of a bone substitute material led to higher values in all evaluated micro-CT parameters, except in the bone surface/volume ratio parameter. No significant statistical difference was found for new bone formation between the four groups (P < .05; CI 95%). At all periods, the HA/TCP-A group had a higher percentage of new bone formation. Conclusion These results suggest that a porous hydrophilic surface in the presence of bone substitute material can accelerate peri-implant bone tissue formation.
Keywords: bone grafting; cell viability; osseointegrated dental implantation